Cultural Identity of North Maluku in Folk Pop: When Traditional Meets the Future - Mahmud, Fitriningsih Pratiwi; Talaohu, Ahmad Rifani (Anaphora : Journal of Language, Literary, and Cultural Studies, 2023)
North Maluku, which located in the eastern part of Indonesia is known for its rich cultural diversity that has been established for centuries. There are many traditions and arts that are represented as part of its cultural expression, in which one of them is music. There are several genres of music that are popular among local residents, from traditional, such as Baronggeng music to modern, such as pop, dangdut, and rock. Amongst these variety of music genres, there is one genre that is able to attract the attention of people outside North Maluku, namely Folk Pop. Interestingly, one of the figures who is quite active in expressing North Maluku identity through this Folk Pop genre is a group of young people who are members of a local music group known as TreesHome. However, a question arises when considering whether or not the identity presented by TreesHome reflects the cultural identity of North Maluku Therefore, the study aims to attest how TreesHome is able to maintain the cultural identity of North Maluku in in each music video clip and each of their stage acts. This study is qualitative descriptive research, and by using Identity Theory approach by Stets and Burke (2022), the study will examine and analyze the aforementioned problem. From the analysis result, can be concluded that TreesHome is able to express elements of North Maluku’s cultural identity through a combination of 7 out of 11 ethnic cultural elements proposed by Salter & Harpending (2013) with modernization in the Folk Pop music genre that they present which ultimately provides added value to the cultural identity of North Maluku. Overall, the research can contribute in development of strengthening North Maluku’s cultural identity through Folk Pop by combining traditional and modern music performance.